The Relationship between Workplace Incivility and Emotional Exhaustion of Frontline Employees: The Moderating Role of Self-Efficacy - Nguyen Hong , Quan; Vu Phuong , Linh; Pham Ngoc , Anh; Vu Quynh , Chi; Nguyen Kim , Thanh; Duong Minh , Hang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The purpose of this study is to point out the adverse impacts of workplace incivility on frontline employees’ well-being and the moderating ability of self-efficacy which makes this factor a potential solution. The study is performed by quantitative methods through data of 316 frontline employees in the financial services field in Hanoi, Vietnam using online survey. Collected data are processed through steps of reliability analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), structural equation modeling (SEM), and hierarchical multiple regression analysis for moderating effects. Recommendations including zero-tolerance policy for workplace incivility and programs that help improve self-efficacy for frontline employees are proposed.
Keywords: Frontline employees; Workplace incivility; Supervisor incivility; Customer incivility; Emotional exhaustion; Self-efficacy